Resource selection of moose Alces alces at multiple scales : from trees, plantations and home ranges up to landscapes and regions - Nikula, Ari (The Finnish Society of Forest Science, 2017)
The Moose is a valuable game animal in Fennoscandia but also the most severe pest in forest plantations. In this thesis, I examined factors that affect the habitat selection of moose and moose damage at multiple scales. At the plot level, browsing increased with an increasing number of artificially regenerated pines and deciduous trees taller than pines. The damage risk was the highest in plantations with heavy soil preparation. Moose summer home ranges had more fertile sites than the overall study area. Within summer ranges moose, selected non-pine-dominated habitats and mature forests and avoided human settlements. Winter ranges contained more pine-dominated plantations and other young successional stages, more pine dominated peatland forests and less human settlements and agricultural fields. Within winter ranges, moose used more non-pine-dominated plantations and mature forests and less human-inhabited areas than expected. At the home range level, there were no significant differences between sexes, but within home ranges males and females used different habitats during both seasons. The occurrence of damage in nearby landscape decreased the probability to find a landscape without damage and predicted an increase in the number of damaged plantations. Increased food-cover adjacencies of mature forests and plantations increased damage. An increasing proportion of inhabited areas and the length of connecting roads decreased the number of damage at the landscape sizes of 1 km2 and 5 km2. Moose-damaged stands were concentrated in SW and eastern Lapland in Peräpohja Schist Belt and Lapland s Greenstone Belt with nutrient-rich bedrock. There was less damage in landscapes with an abundant amount of pine-dominated thinning forests. Moose damage plantations were located more on fertile bedrock and soils than undamaged ones. Regenerating Scots pine on fine-grained soils derived from nutrient-rich rocks and naturally occupied by Norway spruce might increase damage risk. Hirvi on Fennoscandian tärkeimpiä riistaeläimiä, ...